A Prolapsed Cecoureterocele in an Adult Treated Conservatively: Highly Rare, but Existent. (14th September 2016) - Löcherbach, Florian; Preusser, Stefan; Meier, Mark
Abstract : Ectopic ureteroceles are one of the most common human urinary tract anomalies. They tend to be recognized and treated in early childhood, especially when they have prolapsed. In most cases surgical therapy is inevitable. In this case report, however, we present the unusual case of a 26-year-old woman suffering from a prolapsed cecoureterocele without any known history of an ectopic ureterocele so far. She was successfully treated without the need for a surgical procedure.